On the exact solutions to some system of complex nonlinear models - Sulaiman, Tukur Abdulkadir; Bulut, Hasan; Baskonus, Haci Mehmet (Walter de Gruyter Gmbh, 2021)
In this manuscript, the application of the extended sinh-Gordon equation expansion method to the Davey-Stewartson equation and the (2+1)-dimensional nonlinear complex coupled Maccari system is presented. The Davey-Stewartson equation arises as a result of multiple-scale analysis of modulated nonlinear surface gravity waves propagating over a horizontal seabed and the (2+1)-dimensional nonlinear complex coupled Maccari equation describes the motion of the isolated waves, localized in a small part of space, in many fields such as hydrodynamic, plasma physics, nonlinear optics. We successfully construct some soliton, singular soliton and singular periodic wave solutions to these two nonlinear complex models. The 2D, 3D and contour graphs to some of the obtained solutions are presented.
Keywords: The extended ShEEM; Maccari's system; Davey-Stewartson equation; soliton solutions